Rede temática de atenção às urgências e emergências na perspectiva de gestores hospitalares - Fonseca, Erika da (2016)
This study aims to analyze the integration of hospitals in the Thematic Network of Attention to Emergencies and Emergencies of the Regional Health Department III of the State of São Paulo - Heart region, from the perspective of their managers. Therefore, the research had based on the assumptions of qualitative research, using semi-structured interviews as the main tool for data collection and content analysis technique for the analysis of interviews. The population consisted of five hospital managers from the four participating municipalities. By analyzing, the data from the reports of managers emerged two categories of analysis: potential (1) and limitations (2). From this definition and following the axes of health care management (axis 1), health management (axis 2) and management in education (Axis 3), subcategories were organized; being identified in the potential three (axis 1), two (2 axis) and two (axis 3) and the limitations two (axis 1), three (axis 2) and (3 axis). For this research, the following considerations had obtained the study allowed not only to identify the perception of managers regarding the Thematic Network Emergency Department and its relationship with its equipment manage, but also the possibility of identifying strengths and weaknesses for effectiveness of proposals proposed regarding the network design. It confirmed the need for strategies to boost the creation / consolidation of the Thematic Network Emergency Department in the Region Heart. Finally, the continuous and permanent reflection of professional, local, municipal, state and federal managers can be a strategy for the consolidation of the Thematic Network.